(untitled) (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Competency in basic knowledge and skill of emergency care is the fundamental goal of all the medical graduates irrespective of their specialty. The aim of this study is to understand the view of young doctors regarding the importance of emergency medicine (EM) both during internship and undergraduate MBBS curriculum. Methods: This was a descriptive cross sectional study conducted at emergency department, KIST Medical College, Lalitpur, Nepal, during 2016 to 2017. Interns were asked to fill up preformed questionnaires to explore the effectiveness of the posting and its necessity to integrate in undergraduate medical education. Results: All the respondent medical interns accepted emergency medicine posting was fruitful. Ninety-six (62.3%) thought one month Emergency Department (ED) posting as appropriate. All the participants thought EM should be included in the undergraduate curriculum (UG). Majority believed it would be appropriate in third year (42%) and final year (42%). One hundred and thirteen (73.4%) wanted to pursue emergency medicine career however 41 (26.6%) were reluctant. Conclusions: All the interns surveyed accepted emergency medicine to be fruitful and should be included in the undergraduate curriculum with one month emergency department posting, and two thirds wanted to pursue it as future career.